Analysis of Factors Influencing Consumer Purchase Decision of Cellular Phones (International Journal of Scientific Research and Management (IJSRM), 2017)
In India, obsession towards cellular phones is increasing continuously. India holds second place in number of cellular phone usage, with the number of 1276660000.Cellular phones have brought immense change in people’s lives, starting from a common man to entrepreneurs. Cellular phone is growing rapidly as a communication tool due to its reach, easy access and cost. In the present scenario, deciding a perfect cellular phone according to our own requirement is quite difficult. Purchasing is not negligible exchange of product from a seller to consumer. Consumers consider purchasing cellular phone as happy affair. They might want to touch, feel and see the phone, and also they want to know more details of the particular choice of their own. There are various internal and external factors which affect consumers purchase decision on mobile phones. There are various studies conducted based on the analysis of factors influencing consumer purchase decision on cellular phones.In this research, the factor which highly influences the cellular phone purchase decision is analyzed. The data will be collected from 300 participants using a structured questionnaire to analyze the highly influencing factor on purchase decision.